Expression of tdTomato and luciferase in a murine lung cancer alters the growth and immune microenvironment of the tumor. - Lei Huang (Public Library of Science (PLoS), 2021)
Imaging techniques based on fluorescence and bioluminescence have been important tools in visualizing tumor progression and studying the effect of drugs and immunotherapies on tumor immune microenvironment in animal models of cancer. However, transgenic expression of foreign proteins may induce immune responses in immunocompetent syngeneic tumor transplant models and augment the efficacy of experimental drugs. In this study, we show that the growth rate of Lewis lung carcinoma (LL/2) tumors was reduced after transduction of tdTomato and luciferase (tdTomato/Luc) compared to the parental cell line. tdTomato/Luc expression by LL/2 cells altered the tumor microenvironment by increasing tumor-infiltrating lymphocytes (TILs) while inhibiting tumor-induced myeloid-derived suppressor cells (MDSCs). Interestingly, tdTomato/Luc expression did not alter the response of LL/2 tumors to anti-PD-1 and anti-CTLA-4 antibodies. These results suggest that the use of tdTomato/Luc-transduced cancer cells to conduct studies in immune competent mice may lead to cell-extrinsic tdTomato/Luc-induced alterations in tumor growth and tumor immune microenvironment that need to be taken into consideration when evaluating the efficacy of anti-cancer drugs and vaccines in immunocompetent animal models.